Pengaruh Kualitas Pelayanan Gojek dan Harga, terhadap Kepuasaan Konsumen pada Layanan Go Ride - Raysha Naya Putri Fadillah; Bunga Karnelia; Nadia Jasmine (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This study aims to analyze the effect of service quality and price on customer satisfaction on Go-Ride services from Gojek. With the rapid development of information and communication technology, online transportation services such as Gojek have become the main solution for people in meeting mobility needs, which require comfort, time efficiency, and affordable prices. High service quality and competitive prices are key factors in creating customer satisfaction. This study uses a qualitative approach with literature studies as the main method, collecting data from various sources such as scientific articles, publications, and related research reports. The results of the study indicate that Gojek's service quality, which includes response speed, punctuality, driver attitude, and safety and comfort during the trip, has a significant positive effect on customer satisfaction. In addition, the price of Go-Ride services also contributes to the level of consumer satisfaction. This study found that customers who experience good service quality tend to be more satisfied and loyal to Gojek services. The results of this study provide important insights for Gojek to continue to improve the quality of its services and maintain competitive prices to meet customer satisfaction, which in turn can strengthen customer loyalty and the company's competitiveness in the online transportation industry.